Interpreting the Concept of Accounts Receivable and Accounts Payable in Accounting Perspective in the Sida Culture of the Manggarai Community: Memaknai Konsep Hutang Piutang Dalam Prespektif Akuntansi Pada Budaya Sida Masyarakat Manggarai - Baso, Susana Purnamasari; Malut, Maria Goreti; Moi, Maria Odriana Veronika (Amkop Management Accounting Review (AMAR), 2025)
This study aims to understand the concepts of debt and credit in the Sida culture of the Manggarai people in East Nusa Tenggara through the perspective of cultural accounting. The phenomenon of SIDA not only reflects economic transactions but also social, moral, and spiritual relationships that reinforce the values of cooperation and solidarity among citizens. The research was conducted using a qualitative ethnographic accounting approach in several villages in Manggarai Regency through in-depth interviews, participatory observation, and documentation of traditions. The results show that the practice of debt in SIDA is not solely an economic motive but also a moral value, a belief, and a social identity. Accounting in this context is not a formal written record, but is manifested in collective memory and social symbols. This study underlines the importance of a contextual approach in understanding local culture-based accounting practices.